Analisis Uji Kuat Tekan Beton pada Campuran Air Payau Desa Tellumpanua Kecamatan Suppa - Andi Yasril Ananta Muliyadi; Hamsyah Hamsyah; Muh. Jabir M3; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Increased economic growth in the city of Parepare with the presence of buildings around the estuary. In general, the composition of concrete making materials is taken from good materials. The problem encountered in the field is that the quality of concrete in construction decreases due to brackish water, causing structural elements in the construction to become porous. Meanwhile, preventive measures are rarely or never taken. As a result, the construction life is very short. Brackish water is one of the causes of structural failure. This is due to the content of sulfate and chloride ions in water containing salt/salts that react with chemical elements in reinforcing steel resulting in corrosion of the reinforcement. The purpose of the study was to analyse the compressive strength of concrete with a mixture of clean water against the percentage of brackish water with a maintenance age of 7, 14, 21, and 28 days. The results showed that brackish water had an impact on reducing the compressive strength of concrete due to the high chemical content in brackish water such as Sulfate (SO²¯) of 52.5 in brackish water in Kenjeran and 62.5 in brackish water in mangrove. Dissolved Solids (TDS) of 15188 mg/l in kenjeran brackish water and 3436 mg/l in mangrove brackish water. Organic Content (KMnO) of 8.05 mg/l in kenjeran brackish water and 6.69 mg/l in mangrove brackish water is too high, so the chemical content contained in brackish water can damage the compounds in the cement content and decrease the strength of the materials contained in the concrete. In this case it can result in concrete having a very low durability.